Specific prodromal symptoms in patients with acute coronary syndrome - Mehdi Heidarzadeh; Shahla Elyaszadeh; Behrouz Dadkhah; Hossein Doustkami (Wiley, 2021)
Abstract Aims Assessing the prodromal cardiac symptoms in patients with acute coronary syndrome (ACS) and compare them with healthy population. Background Identifying specific prodromal cardiac symptoms can play an important role in screening people at risk. Design A comparative study of prodromal symptoms. Methods In this comparison study, an 80‐item checklist of prodromal symptoms was designed and completed by 337 participants in three groups (Patient group I, Patient group II and Healthy group). All participants were studied over a period of six months (from May to October 2017). SPSS‐15 software was used to analyse the data. Results The symptoms of pain/discomfort in chest, pain/discomfort centred in the superior part of chest, pain/discomfort in the left breast and numbness or burning of both arms were the most important symptoms to predict ACS incidence in the two patient groups (odds ratio > 4 and p ≤ .05).